Socio-demographic profile and treatment-seeking behavior of infertile women in tertiary care hospital of Varanasi - Jagriti Annu; Tej Bali Singh; Shikha Sachan; Jigyasa Singh (Discover Public Health)
Abstract Introduction Infertility affects 186 million people globally. According to the World Health Organization report, one in every six people worldwide has experienced infertility at some point in their lives. Treatment-seeking behavior (TSB) refers to the decision-making process of an individual regarding whether to take action or remain inactive upon perceiving a health problem. Understanding the TSB of infertile women is vital for improving the management of infertility. Objective To explore the association between socio-demographic profile and treatment-seeking behavior of infertile women visiting for infertility treatment in a tertiary care hospital. Methods Infertile married women within the age group 18–45 years were enrolled in this study. The data related to TSB and socio-demographic variables were collected through an interview method using a pre-tested structured proforma. The frequency and percentage were used in the description of the background characteristics and TSB. The chi-square test has been applied to test the association between TSB and socio-demographic variables. Results This study highlights that a significant proportion of women experience primary infertility. 60% of women initially preferred government healthcare for infertility treatment, and a notable number (50%) also consulted faith healers for their infertility problem. 28% of infertile women were referred by a physician to this tertiary care hospital. Key findings indicate that age, place of residence, and marriage duration significantly influence treatment-seeking behaviour of infertile women. Conclusion The findings underscore the need for targeted interventions to improve access, raise awareness, and bridge urban–rural and socioeconomic gaps in infertility care, and urgent policy reforms to ensure affordable and equitable infertility care.